Facilitating practices to support children's self-regulation in classrooms: a scoping review protocol. Issue 3 (27th March 2022) - Merritt, Judith; Kernot, Jocelyn; Dizon, Janine; Boshoff, Kobie
ABSTRACT: Objective: The objective of this scoping review is to describe practices for supporting children's self-regulation in the classroom. Introduction: Self-regulation is an integral component of children's well-being and learning in the classroom. Self-regulation is a broad concept that encompasses behavioral, emotional, cognitive, or sensory regulation processes. Children often struggle to self-regulate in class and teachers have difficulty supporting them, which affects children's participation and academic achievement, as well as teachers' self-efficacy and well-being. Inclusion criteria: This review will consider studies that include mainstream primary school children regardless of diagnosis or disability, classroom teachers, and allied health professionals who provide services in mainstream public or private school settings. Self-regulation support practices may include pedagogical, classroom- or curriculum-based practices, environmental modifications, class-management strategies, adult-child relationships, and trauma-informed classroom practices. Methods: The review will be conducted using the JBI three-step search strategy. The databases to be searched include MEDLINE, PsycINFO, Scopus, CINAHL, OTSeeker, and ERIC. Documents from 2010 to the present in English will be included. Data will be extracted and charted by two reviewers using a data extraction tool based on JBI recommendations. Study findings will be presented in tabular or diagrammatic format that aligns with the objective, and a narrative summary will be provided.